Nucleic Acids Conjugates for Biotechnological Applications - Endoh, Tamaki; Rozners, Eriks; Ohtsuki, Takashi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Life in biological systems is maintained by the cooperative actions of various biomolecules. With the development of chemical and biological technologies related to nucleic acids, the details of the mechanisms of such cooperative actions between nucleic acids and other biomolecules have been elucidated and further applied in various applications. In the papers published in this Special Issue, advanced research works involved in nucleic acid conjugates are reported in wide application fields, such as artificial gene regulation, biomolecular sensing, and therapeutics from leading scientists in nucleic acids chemistry and engineering.